## Answer :

[tex]\[ \begin{cases} 3x + 2y = -9 & \quad (1) \\ x = y + 7 & \quad (2) \end{cases} \][/tex]

### Step 1: Solve one of the equations for one variable

Equation (2) is already solved for [tex]\(x\)[/tex]:

[tex]\[ x = y + 7 \][/tex]

### Step 2: Substitute this expression into the other equation

We will substitute [tex]\(x = y + 7\)[/tex] into equation (1):

[tex]\[ 3(y + 7) + 2y = -9 \][/tex]

### Step 3: Simplify the resulting equation

First, distribute the 3 on the left side:

[tex]\[ 3y + 21 + 2y = -9 \][/tex]

Combine like terms:

[tex]\[ 5y + 21 = -9 \][/tex]

### Step 4: Solve for [tex]\(y\)[/tex]

Subtract 21 from both sides to isolate the [tex]\(y\)[/tex] term:

[tex]\[ 5y = -9 - 21 \][/tex]

[tex]\[ 5y = -30 \][/tex]

Divide both sides by 5:

[tex]\[ y = -6 \][/tex]

### Step 5: Substitute [tex]\(y\)[/tex] back into the expression for [tex]\(x\)[/tex]

We found [tex]\(y = -6\)[/tex]. Substitute this value into the expression [tex]\(x = y + 7\)[/tex]:

[tex]\[ x = -6 + 7 \][/tex]

[tex]\[ x = 1 \][/tex]

### Conclusion

The solution to the system of equations is:

[tex]\[ (x, y) = (1, -6) \][/tex]

So, the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex] are:

[tex]\[ x = 1, \quad y = -6 \][/tex]